Constitutional Issues of EU External Relations Law - Gatti, Mauro; Neframi, Eleftheria (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The present book invites the reader to rethink some questions raised in EU external relations law in the light of recent developments in the case law of the Court of Justice, from the perspective of the constitutional foundations of the Union. The various chapters invite the reader to take a look at the balance between the specific legal regime for EU external action and the constitutional fundamentals of the EU legal order such as: the principles of conferral, loyalty, and institutional balance, as well as the rule of law, democracy, and fundamental rights protection. The accommodation between specificity and fundamental principles is, thus, a transversal constitutional issue.